2016
DOI: 10.1093/jxb/erw320
|View full text |Cite
|
Sign up to set email alerts
|

3D deformation field in growing plant roots reveals both mechanical and biological responses to axial mechanical forces

Abstract: HighlightMaximal axial pressures exerted by freely growing roots are restricted by root buckling but are increased when root lateral bracing is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 44 publications
(50 reference statements)
2
31
0
1
Order By: Relevance
“…Furthermore, the different penetration rates of roots (0.004-0.02 mm min 21 ) and the cone penetrometer (4 mm min 21 ) might further influence penetration forces and stresses . However, the penetration forces and stresses as calculated in this study are within the range of previously reported results for different plant species (Misra et al, 1986;Bengough and McKenzie, 1997;Iijima et al, 2003b;Azam et al, 2013;Bizet et al, 2016). .…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the different penetration rates of roots (0.004-0.02 mm min 21 ) and the cone penetrometer (4 mm min 21 ) might further influence penetration forces and stresses . However, the penetration forces and stresses as calculated in this study are within the range of previously reported results for different plant species (Misra et al, 1986;Bengough and McKenzie, 1997;Iijima et al, 2003b;Azam et al, 2013;Bizet et al, 2016). .…”
supporting
confidence: 88%
“…Furthermore, the lack of a root cap results in decreased root elongation rates in comparison with roots with an intact cap (Iijima et al, 2003b;Vollsnes et al, 2010). The forces and stresses that occur at a root tip during soil penetration can be measured directly in soil (Iijima et al, 2003b) or in free air and nutrient solutions (Misra et al, 1986;Bengough and Kirby, 1999;Azam et al, 2013;Bizet et al, 2016). As an alternative, cone penetrometer measurements combined with quantifications of root tip and cone geometry can be used to calculate root tip penetration forces and stresses (McKenzie et al, 2013).…”
mentioning
confidence: 99%
“…The cycle of reduced axial elongation, thickening near the root tip, relief of the axial stress, further root elongation, is repeated every time the root tip experiences a zone of larger impedance and the root proceeds to grow with a thickened section. The root cap being suspected to sense obstacles [50,64], the release of pressure on the root cap could also limit the thigmomorphism response.…”
Section: C) Does Root Thickening Optimize Penetration?mentioning
confidence: 99%
“…9). In the experiment of Bizet et al [64], the obstacle was a force sensor made of a fine glass blade (Fig. 9B).…”
Section: A) Reorientation Of Root Growth Direction Through Lasting Comentioning
confidence: 99%
See 1 more Smart Citation